(untitled) (Swiss Medical Weekly, 2015)
Biomedical informatics (BMI) is an umbrella scientific field that covers many domains, as defined several years ago by the International Medical Informatics Association and the American Medical Informatics Association, two leading players in the field. For example, one of the domains of BMI is clinical informatics, which has been formally recognised as a medical subspecialty by the American Board of Medical Specialty since 2011. Most OECD (Organisation for Economic Co-operation and Development) countries offer very strong curricula in the field of BMI, strong research and development funding with clear tracks and, for most of them, inclusion of BMI in the curricula of health professionals, but BMI remains only marginally recognised in Switzerland. Recent major changes, however, such as the future federal law on electronic patient records, the personalised health initiative or the growing empowerment of citizens towards their health data, are adding much weight to the need for BMI capacity-building in Switzerland.